Efektivitas Pemberian Zakat Produktif Sebagai Modal Usaha ( Studi Kasus Pada Badan Amil Zakat Nasional Kota Bengkulu) - Amir Mukadar; Khairul Bahrun; Damaya Sinta; Hesti Setiorini (Universitas Muhammadiyah Bengkulu, 2022)
The purpose of this study was to determine the effectiveness of the implementation of giving zakat as business capital in the National Amil Zakat Agency (BAZNAS) Bengkulu City. This research method uses descriptive qualitative research. Research informants in this study were the leaders and employees of BAZNAS Bengkulu City. Data collection techniques using observation and in-depth interviews. The data analysis technique used is data reduction, data presentation, and verification. The result of the research is the effectiveness of the distribution of productive zakat funds at BAZNAS Bengkulu City since 2020 is the Enterprise strategy, this strategy is said to be effective in distributing zakat because it involves many parties, not only external parties but also internal parties. The stages of zakat distribution include several stages including the preparation stage, assessment stage, program/activity planning stage, program implementation stage, and evaluation stage